PENGARUH OPINION SHOPPING DAN AUDIT TENURE TERHADAP OPINI AUDIT GOING CONCERN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Fadjar Harimurti, Fitria Nurhayati, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2018)
This studyaims to determine how the effecton opinion shopping, audit tenure of going concern audit opinion by size of the company as moderating. This research was conducted in sectors of banking listed in the Indonesia Stock Exchange (BEI) in the period of 2013 to 2016 using a sample of 25 companies. Samples were selected using purposive sampling method with a basic analisis using logistik regression and absolute different value. The samples used in the studywhere 25 of the companys with data obsevartion for 4 years. Based on the analysis results it is revealed that the opinion shopping and audit tenure doesn’t seet to affect towards the going concern opinion. Size of company weaken then the influence of the opinion shopping of the going concern audit opinion namun size of company can not influence audit tenure on going concern audit opinion.Keywords: Audit tenure, opinion shopping, size of company, going concern opinio